2018
DOI: 10.2139/ssrn.3270445
|View full text |Cite
|
Sign up to set email alerts
|

Simple Games Versus Weighted Voting Games: Bounding the Critical Threshold Value

Abstract: A simple game (N, v) is given by a set N of n players and a partition of 2 N into a set L of losing coalitions L with value v(L) = 0 that is closed under taking subsets and a set W of winning coalitions W with v(W ) = 1. Simple games with α = min p 0 maxW ∈W,L∈L p(L) p(W ) < 1 are exactly the weighted voting games. We show that α 1 4 n for every simple game (N, v), confirming the conjecture of Freixas and Kurz (IJGT, 2014). For complete simple games, Freixas and Kurz conjectured that α = O( √ n). We prove this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Our proof relied on Lemma 15, which in itself has another consequence. Viewing clutters as simple games, Hof et al [16] showed that given a clutter C over n elements, its critical threshold value is always at most n 4 , and this maximum is achieved if, and only if, C has a fractional packing of value n 2 and b(C) has a fractional packing of value 2. Thus by Lemma 15, it is essentially blockers of cuboids that achieve the largest possible critical threshold value.…”
Section: Lower Bounding the Packing Numbermentioning
confidence: 99%
“…Our proof relied on Lemma 15, which in itself has another consequence. Viewing clutters as simple games, Hof et al [16] showed that given a clutter C over n elements, its critical threshold value is always at most n 4 , and this maximum is achieved if, and only if, C has a fractional packing of value n 2 and b(C) has a fractional packing of value 2. Thus by Lemma 15, it is essentially blockers of cuboids that achieve the largest possible critical threshold value.…”
Section: Lower Bounding the Packing Numbermentioning
confidence: 99%